Ethical Discernment Points: The Alchemy of Dialogue, Deliberation, and Decisions - Lehr, Ron; Belgrave, Michael; Watt, Crystal; Hill-Lehr, Andria (Canadian Journal of Counselling and Psychotherapy, 2013)
This paper describes research that explores how counsellors cope with ethically challenging situations, which are referred to in this report as Ethical Decision Points. (EDPs). We explore how counsellors navigate and make decisions about these EDPs, and the degree to which dialogue and conversation with others is part of their discernment process. In this qualitative study, counsellors from across Canada responded to an online ethical scenario that contained several EDPs. Several themes are identified in the analysis that allows us to describe a process employed by counsellors in their ethical decision making. Dialogue is identified as part of the decision process but it is not as prevalent as predicted. We conclude that counsellors include dialogue or talking to others as one step in ethical decision making rather than it being the main component of the process. We present some recommendations for ethics education and counselling practice. Résumé Ce document décrit de la recherche qui explore comment les conseillers font face à des situations éthiquement difficiles, lesquelles seront nommées « points de décisions éthiques » (PDÉ) dans le présent document. Nous allons explorer comment les conseillers s’orientent autour de ces PDÉ, prennent des décisions à leur sujet et à quel point le dialogue et la conversation avec les autres font partie de leur processus décisionnel. Dans cette étude qualitative, des conseillers d’un bout à l’autre du Canada ont réagi par l’entremise du web à un scénario éthique qui contenait plusieurs PDÉ. Plusieurs thèmes sont identifiés dans l’analyse qui nous permet de décrire un processus utilisé par des conseillers dans leur processus décisionnel en ce qui concerne l’éthique. Le dialogue est identifié comme faisant partie du processus décisionnel mais n’est pas aussi prédominant que prévu.  Nous concluons que les conseillers incluent le dialogue ou la discussion comme étant une des étapes du processus de décision éthique plutôt que la partie principale du processus. Nous présentons des recommandations pour l’éducation éthique et les pratiques de conseillance.